2010
DOI: 10.1152/jn.00477.2010
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Intramuscular Activation During Rhythms Produced by Spinal Patterning Systems in the In Vitro Neonatal Rat With Hindlimb Attached Preparation

Abstract: Klein DA, Tresch MC. Specificity of intramuscular activation during rhythms produced by spinal patterning systems in the in vitro neonatal rat with hindlimb attached preparation. J Neurophysiol 104: 2158 -2168, 2010. First published July 21, 2010 doi:10.1152/jn.00477.2010. In intact adult vertebrates, muscles can be activated with a high degree of specificity, so that even within a single traditionally defined muscle, groups of motor units can be differentially activated. Such differential activation might ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Centrally generated two-burst patterns also occur during fictive locomotion in the neonatal rat, and recruitment varies with the form of network activation, i.e. pharmacologic, electrical currents (Klein and Tresch, 2010). Thus, we interpret our findings as significant evidence that proprioceptive input produced by limb movement can modulate centrally generated RLM patterns prior to hatching.…”
Section: Research Articlementioning
confidence: 52%
“…Centrally generated two-burst patterns also occur during fictive locomotion in the neonatal rat, and recruitment varies with the form of network activation, i.e. pharmacologic, electrical currents (Klein and Tresch, 2010). Thus, we interpret our findings as significant evidence that proprioceptive input produced by limb movement can modulate centrally generated RLM patterns prior to hatching.…”
Section: Research Articlementioning
confidence: 52%
“…The spinal cord is positioned dorsal‐up so that stepping can be activated by bath application of neurochemicals (Fig. D–E) to generate coordinated muscle activity patterns with limb kinematics that compare well to what is seen in the adult …”
Section: Introductionmentioning
confidence: 82%
“…1D-E) to generate coordinated muscle activity patterns with limb kinematics that compare well to what is seen in the adult. [12][13][14][15][16] We have since incorporated ventral and dorsal root recordings, as well as intracellular recordings, to relate neural function and behavior in ways not typically possible in vitro. 17 A particularly exciting observation regarding afferent feedback concerned the control of transmission in contralateral afferents by a distinctive form of presynaptic inhibition (PSI), called primary afferent depolarization (PAD).…”
Section: Introductionmentioning
confidence: 99%
“…; Whelan et al . ; Strauss and Lev‐Tov ; Klein and Tresch ; Taccola ) potently activate the hindlimb and body‐stabilizing CPGs in rodents in the absence of supraspinal control. Our studies of the isolated spinal cord of the newborn rat revealed that the sacrocaudal afferent‐induced locomotor rhythm could be blocked by bathing the sacral segments in low‐calcium high‐magnesium Kreb's saline, to suppress synaptic transmission, or by selective application to these segments of the non‐NMDA receptor blocker CNQX (Strauss and Lev‐Tov ) or the mu‐opioid agonist DAMGO (Blivis et al .…”
Section: Electrical Activation Of the Hindlimb‐moving And Body‐stabilmentioning
confidence: 99%